Konsep Ta'abbudi Dan Ta'aqquli Dan Implikasinya Terhadap Perkembangan Hukum Islam - La Jamaa (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
The concept taabbudirelating to matters of worship ma?dah, and taaqqulirelating to the affairs and worship gairu ma?dah. Taabbudiabsolute, static, and its existence is not based on mere outward benefit, while taaqquliis relative, not static, and its existence is based on the benefit to humans so it is rational. However, in each taaqqulidefinitely embodied the values of worship. Instead, at each contained taabbudialso for human benefit. Both of these concepts have great contribution in the development of Islamic law.